Visa challenges at IIUM (2020-2024): bureaucratic hurdles and their impacts on international students’ enrolment - Zaidi, Farah Nur Aisyah; Jamaludin, Farhatun Nisa; Rahmani, Hirzia; Mohd Jamalludin, Nur Hafizah; Abdullah Fauzi, Nurfariha Akmal Fawwazah; Mohd, Siti Hadija (Akademi Tenggara Press, 2025)
This study examines the persistent visa-related challenges faced by international students at the International Islamic University Malaysia (IIUM). It investigates the procedural inefficiencies, financial difficulties, and academic disruptions caused by visa delays, particularly during and after the COVID-19 pandemic. Using a historical research methodology that incorporates oral interviews, surveys, and netnography, the study documents the lived experiences of affected students. Findings reveal that visa delays have led to heightened academic stress, financial strain, and uncertainty regarding legal status, significantly impacting students’ well-being. The study emphasizes the need for enhanced administrative efficiency, improved communication between university authorities and students, and a more transparent visa application process. By contextualizing the issue through a public history lens, this research contributes to ongoing discussions on international student mobility and higher education policies in Malaysia.